2002
DOI: 10.1080/19485565.2002.9989055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the nurturant bonding system on child security of attachment and dependency

Abstract: This paper uses a biopsychosocial theory of human bonding to explore the intergenerational transmission of bonding traits. More specifically, it examines how the nurturant bonding system of the mother affects the succorant bonding system of the young child. In the first section of the paper, we take the bonding framework proposed by Miller and Rodgers (2001) and elaborate its implications for mother-child dyads. Next, we describe the collection of data from 78 mothers prior to their pregnancy with an index chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…These two feelings then have an impact on the woman's parenting behavior and the interactions she has with her infant child, which in turn ultimately affect the attachment security of her 2‐year‐old child. This connection between the woman's motivational substrate for childbearing, which reflects her desire and capacity to bond with a child, and the quality of her 2‐year‐old child's bond with her confirms and strengthens the findings of previous research (Miller et al, 2002, 2008). At the same time it increases our understanding of the psychosocial processes involved in the intergenerational transmissions of patterns of bonding or attachment (George & Solomon, 1999).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These two feelings then have an impact on the woman's parenting behavior and the interactions she has with her infant child, which in turn ultimately affect the attachment security of her 2‐year‐old child. This connection between the woman's motivational substrate for childbearing, which reflects her desire and capacity to bond with a child, and the quality of her 2‐year‐old child's bond with her confirms and strengthens the findings of previous research (Miller et al, 2002, 2008). At the same time it increases our understanding of the psychosocial processes involved in the intergenerational transmissions of patterns of bonding or attachment (George & Solomon, 1999).…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has indicated that being born an unwanted child has long‐term effects on self‐esteem (Axinn, Barber, & Thorton, 1998) and psychiatric status (Kubicka, Roth, Dytrych, Matejcek, & David, 2002) when the child becomes an adult. This study extends the existing evidence (Miller et al, 2002, 2008) that these adult manifestations of unwantedness may be rooted in the preconception readiness of the mother to bond with the child and the effect that her consequent postconception emotional states and behaviors have on the quality of the child's bond with her.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A few studies have already found an association between birth status (or pregnancy wantedness) and attachment style. In one study of 78 middle-class married mothers, Miller, Feldman, and Pasta (2002) assessed attachment security using the attachment Q-Set (Waters, 1995) and found that childbearing motivational traits (wanting to have a baby or not) measured before the conception positively predicted the child’s attachment security at the age of 2–4.5 years. In a different study, Ispa, Sable, Porter, and Csizmadia (2007) studied 173 young, low-income, first-time African American mothers.…”
Section: Introductionmentioning
confidence: 99%